2007
DOI: 10.1016/j.marpolbul.2007.01.018
|View full text |Cite
|
Sign up to set email alerts
|

PCB, PCDD/F and PBDE levels and profiles in crustaceans from the coastal waters of Brittany and Normandy (France)

Abstract: Polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs) and polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) were analysed in the muscle of various edible marine crustaceans (spider crab, edible crab, velvet swimming crab and Norway lobster) from the Brittany and Normandy coasts (France). The highest concentrations were measured in species collected from Antifer (Seine Bay). PCB and PBDE patterns in crustacean muscles were similar and independent of the geographical area with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 44 publications
4
25
0
Order By: Relevance
“…The accumulation of hydrophobic organic chemicals by invertebrates has proven useful in environmental monitoring for polychlorinated biphenyls (PCBs) [1], organochlorine pesticides (OCPs) [2][3][4], polychlorinated benzo-p-dioxins and furans (PCDD/F) [1,5] and organophosphate insecticides (OPs) [3,6,7]. Many of these chemicals are known to cause sublethal effects in aquatic organisms, including reproductive impairment and decreases in hatching success [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of hydrophobic organic chemicals by invertebrates has proven useful in environmental monitoring for polychlorinated biphenyls (PCBs) [1], organochlorine pesticides (OCPs) [2][3][4], polychlorinated benzo-p-dioxins and furans (PCDD/F) [1,5] and organophosphate insecticides (OPs) [3,6,7]. Many of these chemicals are known to cause sublethal effects in aquatic organisms, including reproductive impairment and decreases in hatching success [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the sum of 18 PCB congeners was highest in sea bass collected from Antifer, France. However, at the same sampling location, the PCDD/PCDFs concentration was highest in mussels [17]. In the North Sea, Belgium, ⌺ PCB ranged between 1.5 and 280 ng/g (ww) among benthic invertebrates.…”
Section: Dioxin and Dioxin-like Compoundsmentioning
confidence: 83%
“…Among them, PCB-138 and -153 are the most abundant congeners [20]. Bodin et al [17] found high levels of ⌺ PBDE in sea bass (11,004 pg/g dry weight-dw) from Antifer, France. ⌺ PBDEs ranged between 69 and 1100 pg/g (ww) in muscle of trout from Greenland and European high mountain lakes [21].…”
Section: Brominated Flame Retardants (Bfrs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The total concentration of PBDEs in mussels was 13.8 ng/g lipid in Qingdao coastal sea [11]. A few PBDE congeners (BDE-47, 99, 100, and 28) were found in crustacean muscles (spider crab, edible crab, velvet swimming crab, and Norway lobster) from coastal waters Brittany and Normandy (France) [12]. The total concentration of PBDEs ranged from 0.38 to 9.19 ng/g wet weight in mussels (Mytilus coruscus and M. edulis) and oysters (Crassostrea gigas) [13].…”
Section: Introductionmentioning
confidence: 98%